2014
DOI: 10.1161/atvbaha.113.303081
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Homeostatic Chemokines CCL19 and CCL21 and Their Receptor CCR7 to Coronary Artery Disease

Abstract: CCL19/CCL21-CCR7 is a novel homeostatic chemokine system that modulates human monocyte adhesion and migration, promoting atherogenesis. It is associated with coronary artery disease risk in Chinese Han individuals. These data suggest that the CCL19/CCL21-CCR7 axis plays an important role in atherosclerosis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…CCR7 and its ligands, Chemokine (CC-motif) ligand 19 (CCL19) and 21 (CCL21) have been associated with increased monocyte migration and are associated with increased CVD risk in humans. 34 CCR2, the receptor for monocyte chemo-attractant protein-1 (MCP-1), also enhances chemotaxis 35 and is important in the process of plaque formation in mice. 36 In our study, monocytes of patients with CKD also showed enhanced migratory capacity compared with healthy controls, suggesting that expression of these chemokine receptors in humans may also contribute to the inflammatory status of the arterial wall.…”
mentioning
confidence: 99%
“…CCR7 and its ligands, Chemokine (CC-motif) ligand 19 (CCL19) and 21 (CCL21) have been associated with increased monocyte migration and are associated with increased CVD risk in humans. 34 CCR2, the receptor for monocyte chemo-attractant protein-1 (MCP-1), also enhances chemotaxis 35 and is important in the process of plaque formation in mice. 36 In our study, monocytes of patients with CKD also showed enhanced migratory capacity compared with healthy controls, suggesting that expression of these chemokine receptors in humans may also contribute to the inflammatory status of the arterial wall.…”
mentioning
confidence: 99%
“…For example, CCL19/CCL21-CCR7 axis were associated with risk for coronary artery disease in a Chinese population. 80 …”
Section: Inflammation In Atherosclerosismentioning
confidence: 99%
“…It was also noted that CCL19 influences the activation of leukocytes, lipid uptake of macrophages, and foam cell formation within atherosclerotic plaques. In a recent human coronary atherosclerotic plaque study, 41 immunohistochemical staining of plaques showed CCL19 expression in all stages of atherosclerosis, although levels increased with the development of atherosclerosis. It was also noted that CCL19 was expressed within endothelial cells (EC) and EC dysfunction is the initiation of atherosclerotic development.…”
Section: Discussionmentioning
confidence: 88%